Environmental risk factors for multiple sclerosis: A case-control study in Kerman, Iran - Mahlagha Dehghan; Fatemeh Ghaedi-Heidari (Wolters Kluwer Medknow Publications, 2018)
Background: Several studies have addressed the environmental risk factors for multiple sclerosis (MS). Concerning contradictory results and change of epidemiologic patterns and the role of environmental factors, in the present study, some risk factors, especially environmental factors, on MS were studied. Materials and Methods: This was a retrospective case-control study conducted among 120 patients with MS and 360 healthy individuals in Kerman, Iran. Inclusion criteria included (1) MS disease, diagnosed by a neurologist according to the McDonald criteria, and (2) tendency to participation in the study. Exclusion criteria included (1) suffering from cognitive disorders; (2) incomplete questionnaire; and (3) continuous migration. Data were collected using a questionnaire consisting of personal information and some environmental factors. Data were analyzed using descriptive and inferential statistics. Results: The results showed that diet was associated with a higher risk of MS with the odds ratio (OR) of 14.46 and 95% confidence interval (CI) of 3.02-69.21 (p < 0.001) for vegetarian and OR of 11.74, 95% CI of 4.66-29.57 (p < 0.001) for animal diets. Similarly, vitamin D supplementation contributed to MS risk (OR: 2.27, 95% CI: 1.32-3.89; p < 0.001). In contrast, history of using cow's milk during infancy resulted in a lower risk of MS (OR: 0.33, 95% CI: 0.20-0.52, p < 0.001). Conclusions: This study suggests that different lifestyles including using cow's milk during infancy and avoiding only vegetarian and animal diets may reduce MS risk in southeastern Iran. More studies are suggested to investigate the controversial finding of the negative effect of vitamin D supplementation in this area.